Band gap tuning of perovskite solar cells for enhancing the efficiency and stability: issues and prospects - Miah M.H.; Khandaker M.U.; Rahman M.B.; Nur-E-Alam M.; Islam M.A. (Royal Society of Chemistry, 2025)
The intriguing optoelectronic properties, diverse applications, and facile fabrication techniques of perovskite materials have garnered substantial research interest worldwide. Their outstanding performance in solar cell applications and excellent efficiency at the lab scale have already been proven. However, owing to their low stability, the widespread manufacturing of perovskite solar cells (PSCs) for commercialization is still far off. Several instability factors of PSCs, including the intrinsic and extrinsic instability of perovskite materials, have already been identified, and a variety of approaches have been adopted to improve the material quality, stability, and efficiency of PSCs. In this review, we have comprehensively presented the significance of band gap tuning in achieving both high-performance and high-stability PSCs in the presence of various degradation factors. By investigating the mechanisms of band gap engineering, we have highlighted its pivotal role in optimizing PSCs for improved efficiency and resilience. ? 2024 The Royal Society of Chemistry.